PERANAN KOPERASI SIMPAN PINJAM DALAM MEMBERIKAN KREDIT TERHADAP PENGEMBANGAN INDUSTRI KECIL DI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Herdian, Oki; Harahap, Azwar; Basri, Syafril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of Equity and Equity Credit for the development of small industries in the district of Tanah Putih Rokan Hilir. Research conducted on Small Industrial in Tanah Putih Rokan Hilir.Sampel that serve as respondents drawn using census method in which all of the population used as a sample. Questionnaires were distributed to 23 respondents, and successfully recovered the complete answer is obtained from 23 respondents. Data were collected from 23 respondents further data were analyzed with SPSS version 17.0 using descriptive statistical analysis and multiple linear regression analysis to produce the classic assumption test, model of data analysis, coefficient of determination and prove the hypothesis. The result of research partially and simultaneously discovered that the variable Equity and Capital Credit influence on the development of Small Industries.Keywords: Equity, capital loans and Small Industry